Knowledge, Awareness and Attitude towards Orthodontic Treatment among Patients Visiting the Tertiary Care Center (Nepal Journal of Health Sciences, 2025)
Introduction: While numerous studies have been conducted among high school students and orthodontic patients, limited research has evaluated knowledge, awareness, and attitude regarding orthodontic treatment among general patients seeking dental care. This study aimed to assess these factors among patients attending a tertiary care center.Objective: To assess knowledge, awareness, and attitude toward orthodontic treatment among patients visiting the tertiary care center.Method: A cross-sectional study was conducted among 303 patients attending the Department of Oral Medicine and Radiology, Kathmandu University School of Medical Sciences, Dhulikhel Hospital. Data were collected using a structured questionnaire with dichotomous (Yes/No) responses assessing knowledge, awareness, and attitude toward orthodontic treatment. Descriptive statistics, including frequency and percentage, were calculated, and Chi-square tests were applied to compare responses by gender.Result: Majority of patients demonstrated a good level of knowledge about orthodontics and the effects of malocclusion. However, their understanding of the causes of malocclusion like genetic factors and habits like thumb sucking, tongue thrusting, and mouth breathing was moderate. Additionally, most participants had limited awareness about the importance and use of retainers following orthodontic treatment. While significant number of patients were knowledgeable and aware of orthodontic care, only few were personally motivated to undergo the treatment.Conclusion: Although the findings were encouraging, indicating that patients had a good level of knowledge, attitude, and practice towards orthodontic treatment, there remains a need to enhance patient education on the importance of retainers and to improve motivation for undergoing orthodontic treatment.